Designing and Developing a Framework to Support Information Service Systems WebGIS for Cultural Tourism in Pattani Province - Sangmanee, Wutthipong; Suwanwerakamtorn, Rasamee (Parichart Journal, 2024)
The article aims to design and develop a framework to support information service systems of WebGIS for cultural tourism in Pattani Province, which involves three technologies being integrated to create a platform to display on web pages in conjunction with the MySQL database. The system includes a preliminary module for database management, a travel facilitation function, modules for creating 360-degree panoramic image datasets into virtual tour, and workflow for modeling and function display web-based 3D model features, Additionally, an online map service system is utilized. All modules can function as a WebGIS-based system for cultural tourist attraction environments and as digital media for tourism promotion, thereby generating novel learning experiences for cultural heritage in Pattani Province. The client may easily access their smartphones or computers through a browser or by wearing a headset to visit as if they were visiting that particular area, which creates an innovative and fascinating experience for learning about or traveling in cultural places that have never been visited. The system testing result of the system’s performance aspect had the high-level of performance rate ( = 4.19).